(untitled) (Research, Society and Development, 2022)
The aim of this study was to evaluate the factors associated with the average monthly productivity in endodontic services at Dental Specialty Centers (DSCs) of Minas Gerais. Secondary data were collected: the dependent variable was the average monthly productivity in endodontic services at DSCs, and the independent variables: population size, Human Development Index (HDI), Gini Index, Family Health Program’s (FHP) population coverage rate, DSC type, and accreditation time. 76 DSCs were included. Median values for population size, HDI, Gini Index, FHP coverage, and accreditation service time were, respectively, 67,442.50, 0.732, 0.410, 77.945, and 8.00. The endodontic treatment of single-rooted teeth exhibited the highest median production. Most of the DSCs (61.7%) did not reach the targets set. Population size (p=0.001) and DSC type (p=0.025) were associated with the average monthly productivity. The average monthly productivity in endodontic services at these DSCs was low, which was positively associated with population size and accredited DSC type.